Retirement intentions - Sadauskaite, Raimonda (Psihološka obzorja (Ljubljana), 2023)
While the population of Europe is rapidly aging, extended working life has been increasingly promoted. However, a fair amount of older workers prefer to retire early. The question is, whether we know enough about what makes people want to retire as soon as they can. Research on the relationship between the quality of work and retirement intentions has received significant attention but delivered ambiguous results, which may mean that the relationship between retirement intentions and the quality of work is more complex, i.e. moderated by other constructs. Therefore, using data obtained from the seventh wave of the Survey of Health, Ageing and Retirement in Europe (SHARE), we assess the relationship of the retirement intentions with the quality of work, and personality traits. In addition, we investigate whether personality traits moderate the relationship between retirement intentions and the quality of work. We found that physical demands, psychosocial demands, social support at work, control, and reward predict retirement intentions. Neuroticism, extraversion, and agreeableness predict retirement intentions too. The relationship between the quality of work and retirement intentions is not moderated by personality traits.
Keywords: kakovost dela; namera po upokojitvi; osebnostne lastnosti; personality traits; quality of work life; retirement; retirement intentions; upokojitev